COMPARATIVE ANALYSIS OF MOTOR ABILITIES OF TWO GENERATIONS OF FOOTBALL PLAYERS - Bogdan Tomić; Miroslav Smajić; Miroslav Radoman; Peko Vujović; Goran Ivančić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
Good knowledge of athletes and their abilities, that achieve superior results may be a landmark and milestone in what direction should be focused on selection and training process. The various disciplines determine the development of various motor abilities, and be for each sport to define their standards. Motor abilities are subject to weather changes, due to which standards have limited time. The aim of this research was to perform comparative analysis of motor abilities of two generations of football players. The sample comprised 54 players age 23.74 years, who are members of FK Vojvodina Novi Sad divided into two groups. The first group consists of 26 players aged 24.57±2,55 years from the season 2004/2005, while the second group of 28 players aged 22.96±2,86 years from the season 2010/2011. Sample measures for the evaluation of morphological characteristics are: deep forward bend, Abalakov test, push-ups and raising troops. To determine the difference between the two groups of players applied the t-test. Two generations of football players tested, do not differentiate the average value of any variable applied but there was a tendency for the football players second groups showed generally higher values in all tests.